2007
DOI: 10.1111/j.1365-2672.2007.03350.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel genotypic test for rapid detection of multidrug-resistantMycobacterium tuberculosisisolates by a multiplex probe array

Abstract: Aims:  To develop and evaluate a novel genotypic test for rapid detection of rifampicin and isoniazid resistance of multidrug‐resistant (MDR) Mycobacterium tuberculosis isolates by a multiplex probe array. Methods and Results:  A multiplex probe array was designed for genotypic test to simultaneously screen the mutations of rpoB, katG, inhA and ahpC genes, associated with rifampin and isoniazid resistance in M. tuberculosis, with a probe detecting one of the recently confirmed genetic markers of isoniazid resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…Zhang and coworkers developed a similar multiplex probe array including specific oligonucleotide probes aimed to detect relevant mutations in rpoB, katG, inhA, and ahpC genes. The test, which did not use TMAC in the hybridization step, showed a sensitivity and specificity of 88.5% and 100%, respectively, for RIF resistance and 86.5% and 100% for INH resistance compared with DST (24,33). These values are in agreement with the RIOT test here described.…”
Section: Discussionsupporting
confidence: 78%
“…Zhang and coworkers developed a similar multiplex probe array including specific oligonucleotide probes aimed to detect relevant mutations in rpoB, katG, inhA, and ahpC genes. The test, which did not use TMAC in the hybridization step, showed a sensitivity and specificity of 88.5% and 100%, respectively, for RIF resistance and 86.5% and 100% for INH resistance compared with DST (24,33). These values are in agreement with the RIOT test here described.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, we suggest the inclusion of an L533P mutant probe to improve the accuracy and turnaround time of detection of RIF resistance. In addition, although mutations in the oxyR-ahpC intergenic region have been shown to be associated with INH resistance (3,13,14,16,18,19,25), detection of this region was not generally included in molecular methods. Of the 18 MDR isolates possessing mutations in the ahpC gene, 8 harbored the ahpC CϪ10T mutation, which has been described relative to the ahpC mRNA initiation site (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although several assays have focused on the S315T mutation of KatG Zhang et al, 2007;Tho et al, 2011), which is known to confer high-level resistance to INH and be present in as many as 90% of resistant Mtb isolates in Russia (Marttila et al, 1998;, the study by Ando and colleagues showed that other mutations in the KatG gene can cause high-level resistance and those should be included in molecular assays targeting the katG gene (Ando et al, 2010).…”
Section: Molecular Detection Of Resistance Markersmentioning
confidence: 99%
“…Several investigators have focused their efforts in developing assays similar to the MTBDRplus assay to include resistant marker to more than one class of antituberculosis drugs and for more than one mutation per gene target (Sekiguchi et al, 2007;Zhang et al, 2007;Ong et al, 2010;Pholwat et al, 2011).…”
Section: Molecular Detection Of Resistance Markersmentioning
confidence: 99%